SOSIALISASI DAN PELATIHAN PEMBUATAN SABUN BATANG HOMEMADE KEPADA SEKOLAH PEREMPUAN DI DESA KEDUNGSUMBER KABUPATEN GRESIK - Sri Setyaningsih; Sani Rusminah; Mukhtarul Anam (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Increasing the capacity of women is able to have an influence on the development and welfare of an area. One of the government programs socialized as a Clean and Healthy Lifestyle movement is through the movement of washing hands with soap. This service activity aims to assist women in the Women's School Group in an effort to encourage increased knowledge, skills and attitudes in entrepreneurship through training in making commercial soap that is suitable for sale. The presentation was conducted so that participants could know theoretically about soap. The material presented was general knowledge of soap about the function of soap, saponification, SAP, the main ingredients of soap making, additives, manufacturing processes, and work safety. During the activity, participants took an active role in lecture, practice, and discussion sessions. In the process of making soap, which begins with weighing the ingredients, mixing the ingredients, and printing the soap, the participation of the participants is good. Participants' knowledge of soap making knowledge and skills increased. Participants who have an understanding with a value of > 80 as many as 28 people. Participants' skills in making soap can be observed from the soap produced. The soap made has been successful and can be used well.